Analysis of Scraper Conveyor Chain Drive System based on Matlab and VB - Mao Jun; Dong Xianrui; Lu Jinnan; Liu Xifu; Yan Jianglong (Jixie chuandong)
In order to improve the efficiency and reliability of the scraper conveyor chain drive system parametric design,the finite element mathematical model is built and the parametric analysis and calculation is carried out by using the software interface of optimizing design for scraper conveyor developed on the basis of VB by calling database information and using com pieces interface technology of Matlab. The example analysis shows,the professional parametric analysis software,not only can conduce to users who are unfamiliar with the Matlab software,but also make it more convenient for researchers to further Matlab secondary development. And the analysis of scraper conveyor is simplified,the efficiency of the analysis and designand the reliability of the scraper conveyor are improved. The designing of the software can analysis the two conditions of the scraper conveyer,which are load and failure load. Moreover,the scraper conveyor chain jammed failure load tension variation distribution and velocity variation distribution are analyzed,which provides some reference value for the research of super heavy high- power scraper conveyor chain drive system.